Key Conceptual and Practical Considerations of LTA in Term of LTS - Al-ossmi, Laith H.; AL-Mimar, Hanadi F. (European Scientific Journal, ESJ, 2017)
This paper is based on the assumption that the Land Tenure Administration (LTA) and the Land Tenure Security (LTS) are necessary to safeguard and protect the people rights and hence to provide the security of tenures. In this paper, Iraqi objectives of tenure were explored in detail in order to build an understanding of the concepts of LTA and LTS conducted in this research. Therefore, this paper is designed to provide an overview of the key evidence linked to the LTA and LTS aspects. In this context, land tenure types and how they are administered in different purpose and situations, and definitions of the key issues in both of rights and of the security levels were identified.